Resourceful Photosynthesis System and Stem Reserve Accumulation Plays Decisive Role in Grain Yield of Kodo Millet (Paspalum scrobiculatum) - Kumar, P.; Sao, A.; Thakur, A. K.; Yadav, S. C.; Sahu, P. (Indian Journal of Hill Farming, 2018)
Looking for climate resilient potential, experimental analysis was made among forty three advanced breeding lines to interpret the stress tolerance mechanism and homogenize crop improvement parameters for widespread economic domestication of the hill crop. The maximum canopy length was observed in genotype BK 31 (74 cm) followed by BK 6 (73cm), BK 48 (68), BK 2 and BK 23 (64 cm each). Perusal of flowering span revealed that entries exhibiting 50 percent flowering by 65-75 DAS, beard good crop yield. In contrast, vary early blooming genotype (PCGK-18, 50 DAS; PCGK-8 & 19, 50 DAS; PCGK-13, 59 DAS) exhibited comparative lower yield owing to exceedingly short vegetative phase. Among early maturing accessions, PCGK-18 (81 DAS); PCGK-8, PCGK-16 and BK-60 (94 DAS) and others in similar category suffered from yield penalty. Hence, genotypes should be bred for 100-105 DAS to optimize yield potential. PCGK-18 (5.50 kg/ha), BK-81 (8.50 kg/ha), PCGK-15, BK-23, BK-28 (9.0 kg/ha each) and other similar genotypes with lower biomass did not attain optimum yield bar. Conclusively, optimal vegetative growth is fundamental for grain yield physiology and yield increases in accordance to total biomass following normal distributional curve. Analysis of harvestable yield interprets that, higher the canopy length higher the yield. Genotype BK 48 with 70.50 cm plant height, turned to reproductive phase by 76 DAS, accomplished crop cycle by 111 DAS, produced significant higher biomass and maximum yield. During primary development phase, the plant generative organs are well protected by vegetative tissues and unless the stress is semilethal or lethal, the reproductive cells and or structures respond to unfavorable conditions indirectly, as mediated by the vegetative plant organs.